Space Experiences of Women with Visual Impairment in Domestic Architecture - Indrati Prastiti; Arina Hayati; Murni Rachmawati (IPTEK Journal of Proceedings Series, 2020)
Domestic space is where basic human needs are accommodated and understood to the function and its inhabitants. The basic understanding of using domestic space is human activities as a system of activity and areas as a system of settings. However, visual representation techniques in architecture have led to the discriminatory practices towards visually impaired who have limitations on the sense of sight as a primary tool in spatial perception. Thus, studies are necessary to explore the use of domestic space by visually impaired. This paper aims to study the experience of people with visually impaired doing their activities and using a domestic architecture based on the cognition and percetption of their senses. This phenomenological research is studied at the natural setting of domestic housing from the perspective of women with visual impairment who live in Surabaya. The participants are chosen who have actively and independently carried their daily activities in domestic space. The results of this study show women with visual impairment have a specific system of activities and system of settings related to how the senses affect the spatial behavior of visually impaired in accommodating their activities. By doing so, they are able to compromise and create a friendly and accessible domestic environment.